Macross plus. Volume 2, Parts 3 + 4 [videorecording (DVD)] - Kawamori, Shōji, 1960- (Manga Entertainment, 1999)
The rivalry between Isamu Dyson and Guld Bowman reaches boiling point amid the pressure of the Super Nova test program. Myung Lone is torn between her feelings for the two men as her memories of the past on planet Eden are shattered by reality. Angered by the news that the Stealth Valkyrie trials have been abruptly stopped, Isamu and Yang head toward Earth to get even with Valkyrie. Guld, also hearing the same news, goes after them for a final battle. During this fight, Guld recalls the event that had been sealed in his memory. Meanwhile, Sharon Apple takes control of Myung's thoughts and twists them so that she now has full control over the city as well as the minds of its citizens.